2020
DOI: 10.1177/2192568220962435
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Ejaculation After Lumbar Spine Surgery: A Claims Database Analysis

Abstract: Study Design: Retrospective cohort. Objectives: Delayed ejaculation (DE) is a distressing condition characterized by a notable delay in ejaculation or complete inability to achieve ejaculation, and there are no existing reports of DE following lumbar spine surgery. Inspired by our institutional experience, we sought to assess national rates of DE following surgery of the lumbar spine. Methods: We queried the Optum De-identified Clinformatics Database for adult men undergoing surgery of the lumbar spine between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Critical components of the history intake include medical, surgical, psychiatric, sexual, social, and religious history. Medical history should include conditions associated with neuropathy, metabolic derangements, or trauma; surgical history should include the history of neurologic and pelvic procedures [ 49 ]. To date, no studies have identified an association between orgasmic dysfunction and recreational drug use, pornography use, or painful intercourse, but these still represent important components of the social history.…”
Section: Patient Evaluation and Diagnosis Of Domentioning
confidence: 99%
“…Critical components of the history intake include medical, surgical, psychiatric, sexual, social, and religious history. Medical history should include conditions associated with neuropathy, metabolic derangements, or trauma; surgical history should include the history of neurologic and pelvic procedures [ 49 ]. To date, no studies have identified an association between orgasmic dysfunction and recreational drug use, pornography use, or painful intercourse, but these still represent important components of the social history.…”
Section: Patient Evaluation and Diagnosis Of Domentioning
confidence: 99%
“…Ejaculatory disorders (ED) are a commonly cited complication occurring in lumbar spinal surgeries, thought to occur primarily due to hypogastric plexus injury during access to the surgical corridor [40]. Factors associated with an increased risk of ED are obesity [8] and use of BMP. Neuroinflammation is a side effect of BMP investigated by the Food and Drug Administration (FDA), with indications that its use near the hypogastric plexus could result in complications arising from compound leakage.…”
Section: Rates Of Rementioning
confidence: 99%
“…Disorders of ejaculation may be a manifestation of sexual dysfunction in male patients following spine surgery. In a recent large retrospective review, authors found an overall incidence of 0.09% of delayed ejaculation following spine surgery, with ALIF portending the highest risk of delayed ejaculation at a rate of 0.13% [18]. Older male patients are at higher risk of retrograde ejaculation, while in younger male patients, such as those undergoing scoliosis deformity correction, damage to these sympathetic nerves may cause priapism due to unopposed parasympathetic activation [2,19].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…Although pharmacologic interventions exist for the treatment of retrograde ejaculation, anejaculation is more difficult to manage and represents a more serious complication of sympathetic neuronal disruption. While rare, these complications can be considerably distressing to patients and should be identified during routine patient visits postoperatively [18].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%